Uso de los recursos informáticos y de comunicación en el proceso de enseñanza del programa de contaduría pública - Yair Rolando Casadiego-Duque; Gerson Rueda-Vera; William Rodrigo Avendaño-Castro (Mundo Fesc)
The objective was to analyze the use of information and communication resources for teaching by instructors in the Public Accounting program at Francisco de Paula Santander University. Methodologically, the research was quantitative and correlational. The sample consisted of 50 instructors from the aforementioned program. The instrument used was a five-choice Likert-type questionnaire. The results show that, in their use of ICTs, 86.0% of instructors provide planning; 90.0% provide support for information searches; and 86.0% provide support for consulting electronic books in the accounting field, as well as accounting research articles (92.0%). It was concluded that these resources are oriented toward the following aspects: motivational, content, educational and methodological, organizational, control, and evaluation.